First report of fatty acid-derived alkaloids produced by species of the ladybird genus Scymnus (Coccinellidae: Coleoptera) - Magro, Alexandra; Ramon-Portugal, Felipe; Touboul, David; Borges, Isabel; Hemptinne, Jean-Louis (Comptes Rendus. Chimie, 2023)
Species in the genus Scymnus Kugelann are common, but there is little information available on their defence compounds. Pupae are covered with setae on tips of which there are small droplets of liquid. This study explored the patterns of the distribution of the droplets and the influence of diet on their production in five species of Scymnus. GC-MS analyses were used to determine the chemical identity of droplets.All these species produced droplets, but the patterns in the distributions varied among species. Preliminary data indicates a de novo synthesis of the droplet compounds by these ladybirds. The results of the GC-MS analyses suggest that Scymnus spp. produce azamacrolides, which are fatty acid-derived alkaloids.